Autor telewizyjny? Przypadek Matthew Weinera - Flagmańska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
American critics often refer to showrunners as television auteurs. Do showrunners deserve this title? Applying the assumptions of François Truffaut’s la politique des auteurs, as well as Andrew Sarris’s auteur theory, this article discusses the case of Matthew Weiner, the showrunner of Mad Men, a television series set in the 1960s America. Examining each stage of the show’s production process allows to prove that Weiner had decisive influence on scripts, direction, casting, cinematography, costume and production design, music and the editing of his project. Perhaps it is time to stop considering series as a collective work – due to the differences between director’s role in film and in television – and instead focus on its auteur features, since it can be argued that we owe the latest golden age of television to the increase in the showrunners’ creative autonomy.